2005
DOI: 10.1073/pnas.0406814102
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila neuropeptide F and its receptor, NPFR1, define a signaling pathway that acutely modulates alcohol sensitivity

Abstract: Alcohol is likely to affect neurons nonselectively, and the understanding of its action in the CNS requires elucidation of underlying neuronal circuits and associated cellular processes. We have identified a Drosophila signaling system, comprising neurons expressing neuropeptide F (NPF, a homolog of mammalian neuropeptide Y) and its receptor, NPFR1, that acutely mediates sensitivity to ethanol sedation. Flies deficient in NPF͞NPFR1 signaling showed decreased alcohol sensitivity, whereas those overexpressing NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
198
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(208 citation statements)
references
References 34 publications
10
198
0
Order By: Relevance
“…Like its mammalian counterpart neuropeptide Y, NPF is primarily known for its role in feeding behavior [86], but is also involved in several other behavioral processes including mating behavior-associated activity [87][88][89], sleep [90], aggression [91], and ethanol sensitivity [92]. Dipteran NPF expression is observed in larval and adult brain tissue and endocrine cells in the midgut [93,94].…”
Section: Neuropeptide Fmentioning
confidence: 99%
“…Like its mammalian counterpart neuropeptide Y, NPF is primarily known for its role in feeding behavior [86], but is also involved in several other behavioral processes including mating behavior-associated activity [87][88][89], sleep [90], aggression [91], and ethanol sensitivity [92]. Dipteran NPF expression is observed in larval and adult brain tissue and endocrine cells in the midgut [93,94].…”
Section: Neuropeptide Fmentioning
confidence: 99%
“…Many biological phenomena contribute to ethanolinduced responses. These include the involvement of neuropeptide-Y related pathways, [1][2][3][4] glutamate receptors, 5,6 GABA receptors, 7,8 the cAMP signalling pathway, 9,10 the BK potassium channel, SLO-1 [11][12][13] , and membrane perturbation. 14 Many genes and proteins are conserved between Caenorhabditis elegans and humans, including many of those that have been identified as playing a possible role in the effects of ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…The PI is a major locus of peptidergic neurons (Park et al, 2008). Neuropeptides modulate neuronal activity or other cellular properties and have been linked to many types of behavior, including ethanol responses (Corl et al, 2005;Wen et al, 2005;Nässel and Winther, 2010). We observed that downregulating tank in four different classes of peptidergic cells within the PI, including insulin-producing cells that were implicated previously in ethanol sensitivity (Corl et al, 2005), did not affect ethanol sedation.…”
Section: Discussionmentioning
confidence: 99%
“…As in humans and rodents, lower doses of ethanol stimulate locomotor activity in flies (Wolf et al, 2002), whereas higher doses induce motor incoordination and sedation (Moore et al, 1998;Rothenfluh et al, 2006). Many evolutionarily conserved genes regulate acute ethanol responses in both flies and mammals, such as protein kinase A (Moore et al, 1998;Thiele et al, 2000), epidermal growth factor receptor (EGFR) (Corl et al, 2009), and neuropeptide F/Y (NPF/NPY ) (Thiele et al, 1998;Wen et al, 2005). Drosophila also offers powerful tools for studying neural circuits (Kaun et al, 2012); however, the neurons mediating ethanol sedation in flies are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation